Digital natives: A systematic review of the digital health literacy and influencing factors among Chinese college students - Jiajun Jiang; Mei Zhou; Zhihua Yin; Yuqing Cui; Sishuai Liu (Digital Health)
Objective This study aimed to explore the current status of digital health literacy (DHL) among Chinese college students, and to summarize and analyze the related influencing factors. Methods A systematic search was conducted in Web of Science, PubMed, EBSCO, Scopus, China National Knowledge Infrastructure, Wanfang Data, and VIP databases for relevant literature published between 1 January 2006 and 30 May 2024. Results A total of 32 articles, with sample sizes ranging from 224 to 16,497 participants, were included in this review. The e-Health Literacy Scale was the most commonly used measurement for DHL among China college students. The level of DHL among Chinese college students was not high, which was associated with a variable of factors. Based on the social ecological model, the influencing factors at the individual level included age, gender, depression and anxiety status, self-rated health status, frequency of physical exercise, participation in health club activities, taking health courses, and attitude toward health; at the interpersonal level, the influencing factors included family income, parents’ education level, family structure, and only child status; at the organizational level, influencing factors included major, grade, and interpersonal relationships; at the community level, influencing factors included hukou and place of origin. Conclusions The findings of this review provide valuable insights for the development of targeted health education interventions and policies to enhance DHL among Chinese college students. Future research should prioritize nationwide studies to further investigate the factors influencing DHL among Chinese college students and to develop more scientifically rigorous and effective measurement tools for DHL.